Numerical investigation of hydraulic fracture network propagation in naturally fractured shale formations. (March 2016) - Zou, Yushi; Zhang, Shicheng; Ma, Xinfang; Zhou, Tong; Zeng, Bo
Abstract: Hydraulic fracture network (HFN) propagation in naturally fractured shale formations is investigated numerically using a 3D complex fracturing model based on the discrete element method. To account for the plastic deformation behavior of shales, the Drucker–Prager plasticity model is incorporated into the fracturing model. Parametric studies are then conducted for different Young's moduli, horizontal differential stresses, natural fracture (NF) properties, injection rates, and number and spacing of perforation clusters. Numerical results show that horizontal differential stress primarily determines the generation of a complex HFN. The plastic deformation of shale can reduce the stimulated reservoir volume; this is more obvious with Young's modulus of less than 20 GPa. In addition, a higher injection rate could largely increase the fracture complexity index ( FCI ). Moreover, increasing perforation cluster numbers per fracturing stage is beneficial for increasing the FCI, but it also increases the potential merging of neighboring fractures, which may lead to non-uniform development of HFN in far-wellbore regions. To achieve uniform development of HFN within a fracturing stage, the distribution of NFs should be fully considered. The results presented here may provide improved understanding of HFN generation and are favorable for optimizing fracturing treatment designs for shale formations. Highlights: 3D DEM-based complex fracturing model for shale formations is presented. Shale plastic deformation decreases the complexity of hydraulic fracture networks. Distribution of natural fractures may determine whether HFN can grow uniformly. Optimized perforation clusters placement enhances uniformly distributed HFN.